Selenoprotein S Attenuates Tumor Necrosis Factor-α-Induced Dysfunction in Endothelial Cells - Siyuan Cui; Lili Men; Yu Li; Yingshuo Zhong; Shanshan Yu; Fang Li; Jianling Du (Mediators of Inflammation)
Endothelial dysfunction, partly induced by inflammatory mediators, is known to initiate and promote several cardiovascular diseases. Selenoprotein S (SelS) has been identified in endothelial cells and is associated with inflammation; however, its function in inflammation-induced endothelial dysfunction has not been described. We first demonstrated that the upregulation of SelS enhances the levels of nitric oxide and endothelial nitric oxide synthase in tumor necrosis factor- (TNF-) α-treated human umbilical vein endothelial cells (HUVECs). The levels of TNF-α-induced endothelin-1 and reactive oxygen species are also reduced by the upregulation of SelS. Furthermore, SelS overexpression blocks the TNF-α-induced adhesion of THP-1 cells to HUVECs and inhibits the increase in intercellular adhesion molecule-1 and vascular cell adhesion molecule-1. Moreover, SelS overexpression regulates TNF-α-induced inflammatory factors including interleukin-1β, interleukin-6, interleukin-8, and monocyte chemotactic protein-1 and attenuates the TNF-α-induced activation of p38 mitogen-activated protein kinase (MAPK) and nuclear factor-κB (NF-κB) pathways. Conversely, the knockdown of SelS with siRNA results in an enhancement of TNF-α-induced injury in HUVECs. These findings suggest that SelS protects endothelial cells against TNF-α-induced dysfunction by inhibiting the activation of p38 MAPK and NF-κB pathways and implicates it as a possible modulator of vascular inflammatory diseases.